Globalisation, Ethnicity and Migration. The Comparison of Finland, Hungary and Russia - Attila Melegh; Elena Kondratieva; Perttu Salmenhaare; Annika Forsander; LaśzloH́ablicsek; Adrienn Hegyesi (Hungarian Demographic Research Institute, 2004)
The main focus of our project was the comparative study of labour migration in a European Union country (Finland), an EU accessing country (Hungary) and a major non-EU country (Russia) in order to reveal and analyse the causes and the geographic and social mechanisms of labour migration into these countries. The main aim has been to deepen our understanding of the social embeddedness of migratory processes in the analysed region in the era of globalisation. The chosen countries are of different sizes and social and economic background, but their different positions in global processes and their similarities which do appear nevertheless make them perfect objects for comparative studies. In order to structure the analysis, focus will be on the following questions: How globalisation and the post-communist transition appear in the migration processes related to the three countries? What economic and social factors can be associated with the drive of migration inflow if we consider regional migration aspects? What is the role of ethnicity in migration? What lessons can be learned from the comparative analysis of legal mechanisms of entering the respective countries? The project and this working paper has been funded by the University Research Corporation International and USAID in the framework of the “Improvement of Economic Policy Through Think Tank Partnership”. This working paper is the result of the joint work of the Demographic Research Institute at the Hungarian Central Statistical Office, Siberian Center for Applied Research in Economics and the Center for Ethnic elations and Nationalism at Helsinki University.
Keywords: 300; Alternde Bevölkerung; Gesundheit; Osteuropa; Ungarn